Peran pengelolaan keuangan pada suatu organisasi: Studi kasus Ikatan Pelajar Pemuda dan Mahasiswa Aceh (IPPMA) Malang - mubarak, israul (Maliki Interdisciplinary Journal, 2024)
The Aceh Malang Student, Youth and Student Association (IPPMA) is a regional organization originating from Aceh Province. This organization is an association of Acehnese students, youth and students who are currently studying for a bachelor's degree in Malang. Like other organizations, IPPMA also has an organizational structure to support this organization to run well. In this study, the author conducted research on the influence of financial management on committee awareness in paying fees for an activity at IPPMA. The results of this research show that good financial management can increase the committee's awareness in paying its dues.